The Influence of Capital Intensity, Advertising Intensity and Transfer Pricing on Tax Aggressiveness - Pradipta, Khairunissa Alika; Irawan, Ferry; Arieftiara, Dianwicaksih (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the effects of capital intensity, advertising intensity, and transfer pricing on tax aggressiveness. Methodology/approach: This study uses a quantitative method that utilizes secondary data obtained from the Indonesia Stock Exchange (IDX) and related company websites. The data source in this study is the financial reports of food & beverage sub-sector companies listed on the Indonesia Stock Exchange in 2019-2022 as many as 95 companies. Then, the sampling technique uses the Purposive Sampling method. Results/findings: The results show that the capital intensity variable has no influence on tax aggressiveness, while the advertising intensity variable has an influence on tax aggressiveness, and the transfer pricing variable has an influence on tax aggressiveness. Limitations: The limitation of this study is that the measurement used is the Book Tax Difference (BTD), which cannot maximally identify tax aggressiveness. This is because the measurement can only measure the difference between fiscal and commercial policies. In this study, only three variables affect tax aggressiveness, and the population of research objects used is still small, so the variables, population size, and observation years used as research objects can be added. Contributions: This research will have a good contribution to the development of knowledge in the fields of financial accounting and taxation.